Workshop on Mapping out a CCAFS R4D Agenda and Strategy for Southeast Asia - Jost, Christine; Sebastian, Leocadio S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Taking off from the convergence meeting of CGIAR Centers and selected partners in December 2013, this regional workshop to mapped out a CCAFS R4D agenda and strategy for Southeast Asia (SEA). The region was added to the CCAFS portfolio (East Africa, West Africa, South America, South Asia) in order to make the program fully global.